FACTORS AFFECTING SECOND LANGUAGE COMPREHENSION ABILITY IN CHILDREN: A SYSTEMATIC REVIEW - Mohd Tahir, Asman Bin (International Journal of Research on English Teaching and Applied Linguistics, 2023)
This systematic review aims to explore the factors that influence children's second language comprehension ability. Second language acquisition in children is a complex process that is influenced by a variety of factors. Understanding these factors can provide valuable insights for educators, parents, and policymakers to optimize language learning strategies and interventions. This review follows a systematic approach by conducting a comprehensive search across multiple databases, including educational, psychological, and linguistic sources. Relevant studies published in the last decade were included in the analysis. The review focuses on children aged 5 to 12 years, as this is a crucial period for language development and acquisition. By combining previous investigations as a more thorough evaluation of the literature, this study used the systematic literature review (SLR) method to address the research issues. The findings reveal several key factors that influence second language comprehension ability in children. Firstly, individual cognitive factors, such as working memory capacity, attention, and executive functions, play an important role in language processing and comprehension. Second, socio-cultural factors, including parental involvement, socioeconomic status, and exposure to a second language in the community, influence language learning outcomes. Thirdly, instructional factors, such as the quality of teaching methods, curriculum design, and classroom environment, have a great impact on children's language comprehension abilities. Based on these findings, this review underscores the need for a comprehensive and holistic approach to improving second language comprehension skills in children. It emphasizes the importance of integrating cognitive, socio-cultural, and instructional factors in language learning programs. In addition, the review also identifies research gaps and provides recommendations for future research to further enhance our understanding of second language acquisition in children.